2021
DOI: 10.3390/diagnostics11122375
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Targeted ‘Liquid’ NGS Panel for Treatment Customization in Patients with Metastatic Colorectal Cancer

Abstract: The detection of actionable mutations in tumor tissue is a prerequisite for treatment customization in patients with metastatic colorectal cancer (mCRC). Analysis of circulating tumor DNA (ctDNA) for the identification of such mutations in patients’ plasma is an attractive alternative to invasive tissue biopsies. Despite having the high analytical sensitivity required for ctDNA analysis, digital polymerase chain reaction (dPCR) technologies can only detect a very limited number of hotspot mutations, whilst a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…It should be noted that the BEAMing assay has been commercialized and it can only be performed by trained personnel in accredited centers. Based on our experience [ 38 ], it is a rather costly technique that involves a complicated and quite laborious protocol, which is probably hard to implement in everyday clinical practice.…”
Section: Techniques Used For Ctdna Detection and Analysis In Early-st...mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the BEAMing assay has been commercialized and it can only be performed by trained personnel in accredited centers. Based on our experience [ 38 ], it is a rather costly technique that involves a complicated and quite laborious protocol, which is probably hard to implement in everyday clinical practice.…”
Section: Techniques Used For Ctdna Detection and Analysis In Early-st...mentioning
confidence: 99%
“…It should be noted that the BEAMing assay has been commercial-ized and it can only be performed by trained personnel in accredited centers. Based on our experience [38], it is a rather costly technique that involves a complicated and quite laborious protocol, which is probably hard to implement in everyday clinical practice. Digital PCR (dPCR) is an exceptionally powerful technique that allows for accurate quantification of rare mutations as it was first demonstrated by Kinzler and Vogelstein who coined the term [32].…”
Section: Techniques Used For Ctdna Detection and Analysis In Early-st...mentioning
confidence: 99%
“…The rate of concordance of these two platforms amounted to more than 98% in the ctDNA from mCRC patients [31]. Kastrisiou et al [35] developed an original cost-effective NGS gene panel based on the hotspots in six genes: KRAS, NRAS, MET, BRAF, ERBB2, and EGFR. Validation of the panel was made using 68 blood plasma samples from 30 mCRC patients with a diagnosis of the first and second disease progression stages.…”
Section: Concordance Between Different Platformsmentioning
confidence: 99%
“…Liquid biopsy is a useful tool not only for the management of NSCLC. Kastrisiou and colleagues had developed a targeted, cost-effective NGS gene panel that could be easily integrated in the day-to-day clinical routine starting from the plasma of patients with metastatic colorectal carcinomas (mCRC) [ 15 ]. The panel allows for the analysis of the hotspots in six clinically mCRC-relevant genes ( KRAS , NRAS , MET , BRAF , ERBB2 , and EGFR ) with a negative and positive agreement of RAS Testing in Tissue and Plasma specimens of 92.8% and 81.2%, respectively [ 15 ].…”
mentioning
confidence: 99%
“…As reported above, NGS multi-gene panel may be useful also to better characterize clinically interesting cases. De Falco and colleagues described two patients with CRC at different stages (pT2N0M0 and pT4cN1cM1), but both of them harbored double concurrent KRAS pathogenic mutations (p.G12D and p.G13D) that are normally mutually exclusive [ 15 ]. Moreover, using an NGS panel, the authors observed that the two tumors also harbored other mutations in PIK3CA , SMAD4 , NOTCH1 , ERBB2 , and EGFR genes, but all of them were different in the two tumors [ 15 ].…”
mentioning
confidence: 99%